Biomedical applications of polyethylene. (September 2019) - Paxton, Naomi C.; Allenby, Mark C.; Lewis, Philip M.; Woodruff, Maria A.
Graphical abstract: Highlights: Polyethylene has been used as a gold-standard biomaterial for surgical implants. Porous high-density polyethylene implants are embedded in routine clinical practice. Further research into tissue in-growth in porous polyethylene scaffolds is needed. Patient-specificity is now being achieved using 3D scanning, modelling and printing. Abstract: Polyethylene has many advantages as a biomaterial for medical implants and has been extensively applied to the fabrication of porous high-density polyethylene implant for facial and cranial reconstruction. Here we review the properties of polyethylene and its applicability to biomedical applications, including the material properties and influence on processing and surface treatments relevant to surgical implants. Following this, we describe the evolution and reporting of polyethylene's clinical use, as commercial products as reported in scientific research literature. Recent publications and commercial activities are now focussing on incorporating patient-specific design and surgical planning to improve clinical outcomes. This article highlights how the current research landscape is moving into a new era of personalised medicine and optimised tissue regeneration.